2019
DOI: 10.1155/2019/9276831
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin Ameliorates Acute Rejection via IRE1α/TRAF2/NF-κB in Rats Receiving Liver Allografts

Abstract: Background Liver transplantation (LT) is currently an effective treatment for end-stage liver disease, but the occurrence of acute rejection (AR) is still the main problem to be solved. The present study aimed to evaluate the effect of gastrodin (GAS) on LT. Methods Rat transplant models were established and divided into SHAM, LT, GAS-L (50 mg/kg GAS), and GAS-H (100 mg/kg GAS) groups. The liver function, inflammatory factors, liver histopathology, survival of rats, number of M2-type macrophages, liver cell ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Oxidative stress causes direct damage to nerve cells through lipid peroxidation and protein oxidation. In addition, it can also mediate mitochondria and other pathways to indirectly induce neuronal apoptosis (Yuan et al, 2019). Interestingly, in this study, gastrodin inhibited TBI-induced neuronal apoptosis in rats.…”
Section: Discussionmentioning
confidence: 48%
“…Oxidative stress causes direct damage to nerve cells through lipid peroxidation and protein oxidation. In addition, it can also mediate mitochondria and other pathways to indirectly induce neuronal apoptosis (Yuan et al, 2019). Interestingly, in this study, gastrodin inhibited TBI-induced neuronal apoptosis in rats.…”
Section: Discussionmentioning
confidence: 48%
“…Experimental studies have confirmed acute induction of palmitic acid leads to ER stress and triggers IRE1α to form the IRE1α/TRAF2/IKK complex, which promotes NF-κB activation [ 36 ]. ER stress is also involved in acute rejection of liver transplantation and lung injury via the IRE1α/TRAF2/NF-κB pathway [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…[9] In addition to the above findings, gastrodin mitigated cartilage degeneration in rats with osteoarthritis. [84] Yuan et al [10] conducted a study to investigate the impact of gastrodin on acute liver graft rejection in rats. The study indicated that gastrodin diminished the severity of acute liver graft rejection by regulating the IRE1α/TRAF2/NF-kB signaling pathway (Figure 2).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Gastrodin a phenolic glycoside isolated from Gastrodia elata Blume is considered a traditional Chinese herbal medicine used to manage neurological disorders such as epilepsy, [1,2] dizziness, [3] and stroke. [4] Gastrodin showed antiinflammatory, [5][6][7][8][9][10] antioxidant, [11][12][13][14] anti-cancer, [15][16][17][18][19][20] and neuroprotective properties. [21][22][23][24][25][26][27] In recent years, many studies were conducted on the chemical nature, sources, and characterization of gastrodin, as well as its different biological properties.…”
Section: Introductionmentioning
confidence: 99%